Growth and External Financing in Latin America - Carmen Reinhart; Guillermo A. Calvo; Eduardo Fernández-Arias; Ernesto Talvi (Inter-American Development Bank, Research Department, 2001)
This paper discusses the economic performance of Latin America in the last decade, paying special attention to growth and the financial sector. In particular, it shows that external factors, such as like U. S. interest rates and the business cycle, play a key role in capital inflows, investment, and growth. As a result, economic growth in the region tends to be fragile and exhibits a high degree of co-movement, i. e. , high cross-country output correlation. This last feature exacerbates fragility, because there is little room for mutual insurance within Latin America in case a country suffers a bad shock, and finance during downturns has to come primarily from outside the region.
Keywords: 330; Wirtschaftswachstum; Kapitalimport; Internationaler Finanzmarkt; Konjunktur; Lateinamerika